“Analizar el impacto de la tenencia de tierras en Ecuador sobre la productividad agrícola y su efecto en el desarrollo económico durante el año 2022” - Quizhpe Cueva, Ariana Stefany (2025)
In Ecuador, more than 64% of agricultural production comes from smallholders, who face resource and technology constraints. In addition, the Agricultural Productivity Index (API) only increased by 1.1% in 2022, with crops such as banana, sugarcane and soft corn contributing negatively. Therefore, the current research has the general objective of evaluating the impact of land tenure in Ecuador on agricultural productivity and economic growth during 2022, through a statistical and econometric analysis, with the purpose of implementing sustainable agricultural practices, conflict resolution and farmer integration. For this purpose, data from the Survey of Continuous Agricultural Surface and Production for the period 2022 were used; a multiple linear regression model was applied to determine the relationship between agricultural productivity and land tenure type, and an Oaxaca (1973) and Blinder (1973) model was used to determine the productivity gap between producers who are tenant farmers and landowners. The main findings indicate that tenant farmers in Ecuador exhibit higher productivity than landowners. Land tenure does not appear to be crucial for productivity, with factors such as irrigation and fertilizer use having a greater positive impact. Furthermore, the productivity gap between tenants and owners is minimal and not significant, suggesting that access to finance and modern agricultural practices are more relevant determinants. Therefore, it is recommended that the authorities focus on promoting agricultural cooperatives and producer associations. These organizations can facilitate access to advanced technology, training and shared resources, which in turn can increase agricultural productivity.